A Novel Rerouting Planning Model for the Terminal Arrival Routes under the Influence of Convective Weather - Ming Zhang; Xianglu Kong; Kai Liu; Xiangyu Li (Journal of Advanced Transportation)
Under convective weather conditions, aircraft rerouting in terminal airspace is essential to ensure flight safety and reduce air traffic delays. Traditional air traffic rerouting approaches do not combine convective weather information using radar image recognition with controller workload, additional fuel consumption, delay loss, time cost, and route length at terminal airspace in tactical ATFM phase for exact rerouting decision. In accordance with the safety and economic principles of the route network in terminal airspace and in consideration of the changes in the speed and height of aircraft in terminal airspace, a multiobjective rerouting planning model is established in this study for terminal airspace under convective weather conditions in tactical air traffic flow management phase. Then traffic simulation is conducted to analyze the capacity and delays of the rerouting in the approach path in Shanghai terminal area. Experimental results indicate that this model can increase airspace capacity and operational efficiency of air traffic compared with the traditional air traffic rerouting approaches.